Influência das concepções europeias na formulação do pensamento urbanístico paulista - Toledo, Rodrigo Alberto [UNESP] (Universidade Federal de Goias, 2012)
This article aims to present a list of the main influences experimented by architects and urbanists to formulate an urban thought of Sao Paulo City. This way, it will be discussed the main issues raised between the first decades of the XX Century until the 1950s, trying to foresee how the engineers and architects worked to incorporate the urbanistic proposals from Europe and the United States. On the first three sections of this article, it will be presented the concepts that effectively impacted the paulista urban thought of the first half of the XX Century: Sanitarism, the pendulum design: between the Mesologic Theory and the Microbian Theory; Camillo Sitte's historicist formulation; Howard Garden Town and the French experience. Our analysis was formulated by having as a reference a broad and systematic literature, documents stored at Arquivo Histórico Municipal de Araraquara (SP), visits to Faculdade de Arquitetura e Urbanismo da USP Library and to Faculdade de Ciências e Letras da Unesp, Araraquara. The analysis shows that two urbanistic planner streams that happened in São Paulo State were clearly influenced by the conceptions that led the urbanistic debates in the first half of the XX Century. So, these conceptions compose a painting of the urban interventions in São Paulo City.
The influence of European concepts in the development of Paulista urban thought
Keywords: Democracy; Participation; Public policies; Urban planning; Urban thought